2017
DOI: 10.1016/j.clinph.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of attention alternation on movement-related cortical potentials in healthy individuals and stroke patients

Abstract: Objective: In this study, we analyzed the influence of artificially imposed attention variations using the auditory oddball paradigm on the cortical activity associated to motor preparation/execution.Methods: EEG signals from Cz and its surrounding channels were recorded during three sets of ankle dorsiflexion movements. Each set was interspersed with either a complex or a simple auditory oddball task for healthy participants and a complex auditory oddball task for stroke patients. Results:The amplitude of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Since these areas correspond to those of the attention networks, interference from the firing of their neurons with firing of neurons involved in motor planning and execution will lead to reduced detection accuracies. In our previous studies [23][24][25], we demonstrated that changes in attention significantly deteriorate MRCP detection in synchronous BCIs, using auditory distractors. Further, classification of different states of attention attains accuracies of 68% but only for EEG channels located over the motor cortex [25].…”
Section: Introduction Rain-computer Interface (Bci) Systemsmentioning
confidence: 81%
See 2 more Smart Citations
“…Since these areas correspond to those of the attention networks, interference from the firing of their neurons with firing of neurons involved in motor planning and execution will lead to reduced detection accuracies. In our previous studies [23][24][25], we demonstrated that changes in attention significantly deteriorate MRCP detection in synchronous BCIs, using auditory distractors. Further, classification of different states of attention attains accuracies of 68% but only for EEG channels located over the motor cortex [25].…”
Section: Introduction Rain-computer Interface (Bci) Systemsmentioning
confidence: 81%
“…Central channels over the motor cortical representation of either leg or arm muscles are also optimal for detecting and classifying lower limb or upper limb movements [50][51][52]. In our previous studies [23,25], we have shown that the temporal features of MRCPs from the motor cortex were significantly influenced under attention alterations. In this way, the outputs of the central channels may be reliably used for detection of attention variations with the intent to provide appropriate neuro-feedback to the user of the BCI system.…”
Section: B Channel Locationmentioning
confidence: 89%
See 1 more Smart Citation
“…The ST and DT (S-DT and C-DT) were defined as low-, medium-, and high-load divided attention tasks, respectively. The paradigm used here is similar to that employed in previous studies [9][10][11] . This paradigm can reduce the effects of mental or cognitive fatigue 18,19) .…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Highload divided attention leads to a reduction in specific features of MRCP 9,10) . For example, in stroke patients, the negativity of MRCP decreases, while pre-phase variability increases 11) .…”
Section: Introductionmentioning
confidence: 99%